Why Class Matters - Sheri Hamilton; Linda Cooper (Universidade de Lisboa, 2024)
This article reviews the role of class in adult education practice and research in South Africa under apartheid and in the post-apartheid era. Historically adult education was orientated towards the black working-class and to oppressed black communities more generally. In the post-apartheid era, oppositional currents in adult education have continued but have shifted focus to inequalities and oppressions other than class such as race and gender. Much of the adult education literature displays a reluctance to engage explicitly with the concept of class and in many cases, class has been dislodged as the primary category of analysis. The article reviews recent sociological debates on race and class and argues that these are relevant for adult education as a field of practice and research. The article argues that class continues to 'matter' if adult education is to realise its potential to contribute to socialist transformation.